Analisis kebutuhan pengembangan bahan ajar mata kuliah literatur Im Daf-Unterricht berbasis pendidikan karakter - Adhima, Fauzan; Siregar, Azizah Hanoum (Fakultas Sastra Universitas Negeri Malang, 2022)
This study aims to determine the needs of students of the German language education study program (PSPBJ) at the State University of Jakarta in terms of developing teaching materials for the Literature im DaF-Unterricht course (learning German literature) based on character education. The focus of this research is on target analysis and learning needs analysis. The research data were obtained through a questionnaire distributed via Google form and interviews with PSPBJ students who had attended the lesson. From this study, it was concluded that UNJ's PSPBJ students who took the DaF-Unterricht Literature lecture were constrained by the absence of teaching materials or student handbooks. These results also show that PSPBJ students need teaching materials in the form of learning modules for the DaF-Unterricht literature course in German and Indonesian. The purpose of these teaching materials is to make it easier for students to understand the material and strengthen character values in learning. The results of this study are expected to be a reference for preparing a syllabus and developing teaching materials for character education-based Im DaF-Unterricht Literature lectures.